Call for Papers: How attractive are political parties and trade unions to young people? - IF and FRFG (Intergenerational Justice Review)
The IGJR publishes articles from the social sciences/humanities, reflecting the current state of research on intergenerational justice. Its editorial board consists of about 50 internationally renowned experts from ten different countries.